2017
DOI: 10.1016/j.mcn.2017.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Thiamine and benfotiamine prevent stress-induced suppression of hippocampal neurogenesis in mice exposed to predation without affecting brain thiamine diphosphate levels

Abstract: Thiamine is essential for normal brain function and its deficiency causes metabolic impairment, specific lesions, oxidative damage and reduced adult hippocampal neurogenesis (AHN). Thiamine precursors with increased bioavailability, especially benfotiamine, exert neuroprotective effects not only for thiamine deficiency (TD), but also in mouse models of neurodegeneration. As it is known that AHN is impaired by stress in rodents, we exposed C57BL6/J mice to predator stress for 5 consecutive nights and studied th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
55
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(71 citation statements)
references
References 64 publications
(79 reference statements)
7
55
0
Order By: Relevance
“…Although this coenzyme of central metabolism of glucose is widely known as the physiologically active derivative of thiamine, behavioral and biochemical changes in the brain may also be due to the action of non‐coenzyme forms of thiamine (Bunik & Aleshin, ; Mkrtchyan et al, ). This view is supported by no significant changes in the brain ThDP levels measured after administration of a high dose of thiamine, which did change stress reactions and hippocampal neurogenesis along with increased levels of thiamine, but not ThDP, in the brain cortex (Vignisse et al, ). It should be noted, however, that from the minor components of the pool, such as thiamine, its mono‐ and triphosphates, and adenylated thiamine triphosphate, only thiamine and its monophosphate are reliably detected in the brain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although this coenzyme of central metabolism of glucose is widely known as the physiologically active derivative of thiamine, behavioral and biochemical changes in the brain may also be due to the action of non‐coenzyme forms of thiamine (Bunik & Aleshin, ; Mkrtchyan et al, ). This view is supported by no significant changes in the brain ThDP levels measured after administration of a high dose of thiamine, which did change stress reactions and hippocampal neurogenesis along with increased levels of thiamine, but not ThDP, in the brain cortex (Vignisse et al, ). It should be noted, however, that from the minor components of the pool, such as thiamine, its mono‐ and triphosphates, and adenylated thiamine triphosphate, only thiamine and its monophosphate are reliably detected in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, studies of the brain action of thiamine and even its membrane-permeable derivatives usually employ administration of high doses of these compounds (Bettendorff et al, 1990;Boyko et al, 2017;Mkrtchyan, Üçal, et al, 2018b;Tsepkova et al, 2017;Vignisse et al, 2017), also modeling clinical applications of thiamine to treat neurodegenerative disorders (reviewed in (Aleshin et al, 2019;Bunik, 2014). In humans, the doses up to 500 mg thiamine thrice a day (Galvin et al, 2010), or of 500 mg thiamine daily during a month (Hawk, Oser, & Summerson, 1955) are reported to be safe.…”
Section: Thiamine Administration Interacts With Diurnal Changes In mentioning
confidence: 99%
See 1 more Smart Citation
“…Vitamin B1: also known as thiamine, is one of the earliest found in vitamins, and its main phosphorylated derivative -dithiophosphoric acid (ThDP) is a necessary cofactor for glucose metabolism, and the energy source of the brain Mainly in the blood, which can affect the brain's energy metabolism, causing central nervous system disease; 2015, Wang D found that thiamine lack of involvement in the brain inflammatory process, including the promotion of microglia activation, CD40 / CD40L, Cytokines IL1, TNF, IL6 and arachidonic acid metabolites increased [6], and the excessive production of inflammatory mediators caused by neurotoxicity; 2017, Vignisse J found that thiamine deficiency can cause damage to brain function metabolism, but Thiamine precursors protect the hippocampal structure from the deleterious effects of free radicals and inflammatory factors, and play a neuroprotective role, and also play a beneficial role in neurodegenerative diseases such as Alzheimer's disease [7].…”
Section: Water-soluble Vitaminsmentioning
confidence: 99%
“…At the same time, single thiamine administration was not enough for ThDP level rapid normalization in the brain tissue of Av-T rats. The data obtained may indicate that the primary reason for the disturbance of redox balance in thiamine deficiency may be a decrease in the intracellular pool of thiamine and its biologically active derivatives, which in themselves are capable to neutralize free-radical compounds [25,28]. However, this assumption requires further experimental proof.…”
Section: Fig 5 Immunoreactivity Of Tpk In the Three Brain Regions Omentioning
confidence: 99%